New isoflavans from the root bark of Erythrina livingstoniana. (September 2016) - Bedane, Kibrom Gebreheiwot; Masesane, Ishmael B.; Majinda, Runner R.T.
Graphical abstract: Highlights: ⿢ Two new isoflavans were isolated from the root bark of Erythrina livingstoniana . ⿢ The structures were elucidated based on spectroscopic data. ⿢ The absolute stereochemistry for the isolated isoflavans was determined by CD and optical rotation measurements. ⿢ Isolation of different enantiomeric forms of isoflavans obtained from the same plant unusual and suggests some isolates may be impure. ⿢ This is the first report on the root bark of the plant. Abstract: The phytochemical study on the root bark of Erythrina livingstoniana has led to the isolation of two new isoflavans namely 7-hydroxy-2⿲-methoxy-[6⿲⿲, 6⿲⿲-dimethylpyrano (2⿲⿲, 3⿲⿲:4⿲, 5⿲)]isoflavan (1 ) and 7, 2⿲-dihydroxy-[6⿲⿲, 6⿲⿲-dimethyl pyrano (2⿲⿲, 3⿲⿲:4⿲, 5⿲)]isoflavan (2 ) together with eight known flavonoids (3 -10 ). Their structures were elucidated on the basis of spectroscopic analyses (1D- and 2D-NMR and ESI-HRMS) and by comparison with literature data.